Palladium-Catalyzed Butoxycarbonylation of Polybromo(hetero)arenes: A Practical Method for the Preparation of (Hetero)arenepolycarboxylates and -carboxylic Acids - Wu, Weilong; Jing, Yongkang; Zhang, Deyi; Yan, Xianghe; Liang, Rong; Lu, Zhiqiang; Ji, Baoming (Synthesis, 2021)
The palladium-catalyzed alkoxycarbonylation of polybromo(hetero)arenes was investigated systematically. The results show that cheap and readily available in situ Pd(OAc)2/rac-BINAP catalyst can catalyze the butoxycarbonylation of various polybromo(hetero)arenes efficiently, and gave (hetero)arenepolycarboxylates with moderate to high yield (59–94%). Using this method, two new compounds, 4,4′-bis(butoxycarbonyl)-1,1′-bi-2-naphthol and dibutyl [2,2′-bipyrimidine]-5,5′-dicarboxylate, are reported for the first time. In addition, the gram-scale preparation of carboxylate and carboxylic acids was successful performed by butoxycarbonylation followed by hydrolysis. This shows the wide scope of substrates and practical applications of the Pd(OAc)2/rac-BINAP catalytic system. Moreover, these carboxylic acids and carboxylates can be used as ligands or structural units to construct MOFs, metal complexes, and COFs etc.
Keywords: polybromoarenes; polybromoheteroarenes; butoxycarbonylation; palladium catalyst; polycarboxylic acid; ligand